COMPARATIVE ANALYSIS OF FILM GENRES’ TRANSLATION MEANING BETWEEN TWO STREAMING VIDEO SERVICES - Raden Roro Shinta Felisia (Asosiasi Dosen Muda Indonesia, 2023)
In recent years, video streaming services have received positive responses. They have language settings for their services, respectively. In video streaming services, subscribers can choose their preferred languages. Those who choose Indonesian can find the interface in Indonesian. The researcher decides to conduct a comparative analysis of the translation meaning of film genres between two streaming video services. The result is that there are similarities and a difference in the translation meaning of film genres. The similarities include six pairs of translation conveying the conceptual meaning. Meanwhile, the difference is found in one pair of translations conveying different types of meaning: one is reflective meaning, and the other is conceptual meaning. Hence, this research is expected to enrich the translation analysis.